Letter: corticosteroid use alongside tofacitinib in OCTAVE Open. Authors' reply. Issue 10 (27th April 2020) - Sands, Bruce E.; Armuzzi, Alessandro; Marshall, John K.; Lindsay, James O.; Sandborn, William J.; Danese, Silvio; Panés, Julián; Bressler, Brian; Colombel, Jean‐Frédéric; Lawendy, Nervin; Maller, Eric; Zhang, Haiying; et al.
Abstract : LINKED CONTENT This article is linked to Sands et al and Peng et al papers. To view these articles, visit https://doi.org/10.1111/apt.15555 and https://doi.org/10.1111/apt.15674 .